Strategi pengembangan layanan perpustakaan perguruan tinggi berbasis teknologi informasi - Muslina nana (UIN Sumatera Utara, 2018)
University Library is an information center for education and research development by supporting facilities and learning activities that function. As a services center provided optimally and efficiently according to the users needs. The improvement and development of University Library services based on information technology is being realized communicatively with users, stimulating a conducive and comfortable atmosphere for librarians and users. Skilled and qualified librarians or have expertise in information technology, active in delivering various attractive information and reaching users. Keywords: University Library services, information technology